Management of Diabetic Foot Ulcer in a Tertiary Level Hospital-Faridpur - Gaddafi, AL; Das, DK; Faruque, G; Islam, Z; Rahman, MA; Jui, FN; Walid, KM; Biswas, A (Bangladesh Heart Journal, 2019)
A descriptive type of cross sectional study among 210 diabetic patients with foot ulcer was carried out in Diabetic Association Medical College during the period of May 2016 to April 2017 and were categorized based on Meggitt-Wagner system to find out the complications, management, below knee amputation rate and mortality rate. The aim of this study was to practise a profile of diabetic foot ulcer (DFU), complications and its management to assess the outcome of the surgical interventions. Majority of the patients were male 112(53%), and most of them 116 patients (55.23%) presented within Wegner grade - 2 and grade-3 diabetic foot ulcers. The duration of diabetes more than 10 years was 116 (55%). 99 (47%) patients out of 210 patients developed diabetic neuropathy. 76 (36%) patients presented with CKD. Lack of awareness about diabetes mellitus and its lower limb complications, poor compliance to the treatment, poorly controlled blood sugar levels, delay in diagnosis, and late presentation to the tertiary care center, associated habit of smoking are all factors which lead to incidence of DFU at an earlier age than that seen in other studies. After admission of diabetic foot ulcer patients, diabetic foot ulcer is classified according to Wagner grading and treated the diabetic foot ulcer patients as the using protocol ’!1.Assesment whether it was conservative or surgical. 2. Optimal blood sugar control. 3. Systemic antibiotic. 4. Moist wound environment. 5. Offloading such as total contact casting. 6. Improves peripheral arterial circulation due to lack of vascularity. 7. Surgical debridement or minor amputation or major amputation. In case of G-4 or G-5 patients, ischemia was treated before debridement or amputation so that vascular circulation improved in the ulcer area and then healing potential was fastened. Bangladesh Heart Journal 2019; 34(1) : 52-57